2004
DOI: 10.1161/01.cir.0000138397.60956.c2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Regurgitation Is an Important Determinant of Right Ventricular Contractile Dysfunction in Patients With Surgically Repaired Tetralogy of Fallot

Abstract: Background-Evaluation of right ventricular (RV) function in patients with pulmonary regurgitation (PR) after tetralogy repair remains challenging because of abnormal RV loading conditions. Methods and Results-We examined 124 patients, aged 21Ϯ11.4 years, who had tetralogy repair at 3.7Ϯ3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(157 citation statements)
references
References 31 publications
8
146
2
1
Order By: Relevance
“…Transannular patch reducing right ventricular systolic function after correction of TOF was independent of age at the time of surgery or at the time of the clinical follow-up examination. 22) In this study, low preoperative arterial oxygen saturation was also an independent risk factor for right ventricular systolic dysfunction after correction of TOF. The reason for this may be as follows: on the one hand, the severity of hypoxemia was an important risk factor for ventricular dysfunction in pediatric patients with TOF; 23) on the other hand, lower preoperative arterial oxygen saturation meant more serious obstruction of right ventricular outflow tract obstruction which in turn made it more likely to receive transannular patch.…”
Section: Discussionmentioning
confidence: 51%
“…Transannular patch reducing right ventricular systolic function after correction of TOF was independent of age at the time of surgery or at the time of the clinical follow-up examination. 22) In this study, low preoperative arterial oxygen saturation was also an independent risk factor for right ventricular systolic dysfunction after correction of TOF. The reason for this may be as follows: on the one hand, the severity of hypoxemia was an important risk factor for ventricular dysfunction in pediatric patients with TOF; 23) on the other hand, lower preoperative arterial oxygen saturation meant more serious obstruction of right ventricular outflow tract obstruction which in turn made it more likely to receive transannular patch.…”
Section: Discussionmentioning
confidence: 51%
“…It should be noted that studies which report good long-term outcome for patients following such corrective surgeries focus on the adaptive quality of the RV, in light of the impending PI (16,17). However, this is in direct contraindication to other studies which have demonstrated the deleterious effect of chronic PI on RV function (3)(4)(5)(6). While most patients do well soon after surgical correction, in the setting of hemodynamically significant PI, some will develop RV Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Following surgical correction, many patients have moderate to severe pulmonary insufficiency (PI) with minimal or no residual pulmonary stenosis (PS). Chronic PI plays a pivotal role in right ventricular (RV) dilatation and dysfunction, following surgical repair of RV outflow tract (RVOT) obstruction (2)(3)(4)(5)(6)(7)(8). Most patients following surgical correction of TOF experience a prolonged asymptomatic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced echocardiographic assessment of RV function, including measurements of myocardial velocities, strain and strain rate, may provide new insight into RV function under abnormal loading conditions [19,20]. Decreased myocardial velocities and strain rate have been reported in patients after TOF repair compared to normal subjects, not only in the right ventricular free wall but also in the septum and in the left ventricular lateral wall [12,20,21]. This important observation suggests that patients after TOF repair may have decreased intrinsic myocardial contractility, not only of the RV, but also of the left ventricle.…”
Section: Volume Overloadmentioning
confidence: 99%